Макроініціатори на основі хітозану - Соломко, Н.Ю.; Будішевська, О.Г.; Долинська, Л.В.; Кудіна, О.О.; Воронов, С.А. (Видавничий дім "Академперіодика" НАН України, 2007)
pH-sensitive hydrogels as copolymers of Chitosan-co-Poly-(N)-vinylpyrrolidone (Chit-PVP) are obtained. Chi-PVP are synthesized by the radical copolymerization of N-vinylpyrrolidone and peroxide-containing salt of Chit and tert-buthylperoxymethylbytendicarboxylate (PM). PM was obtaned by means of the acetylation of tert-buthylperoxymethanol by maleic anhydride.